2016
DOI: 10.1111/jdv.13725
|View full text |Cite
|
Sign up to set email alerts
|

European Guidelines (S1) on the use of high‐dose intravenous immunoglobulin in dermatology

Abstract: Background The treatment of severe dermatological autoimmune diseases and toxic epidermal necrolysis (TEN) with

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
0
27

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(85 citation statements)
references
References 44 publications
0
58
0
27
Order By: Relevance
“…IVIG is thought to prevent Fas‐mediated apoptosis of keratinocytes; however, recent meta‐analyses have concluded that the use of IVIG is equivocal in its benefit, specifically with nine studies showing no survival benefit . However, current European guidelines support the use of IVIG in the absence of alternative evidence‐based therapies . If utilized, IVIG administered at a high dose (total dose ≥2 g/kg) has been shown to decrease mortality compared to low‐dose IVIG .…”
Section: Discussionmentioning
confidence: 99%
“…IVIG is thought to prevent Fas‐mediated apoptosis of keratinocytes; however, recent meta‐analyses have concluded that the use of IVIG is equivocal in its benefit, specifically with nine studies showing no survival benefit . However, current European guidelines support the use of IVIG in the absence of alternative evidence‐based therapies . If utilized, IVIG administered at a high dose (total dose ≥2 g/kg) has been shown to decrease mortality compared to low‐dose IVIG .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, while IVIg has previously been an accepted therapeutic agent in TEN, its efficacy is becoming more questionable. Despite these studies, the current European guidelines on the use of IVIg in dermatology have suggested that it should be used early in the disease process in the absence of an alternative evidence-based therapeutic alternative [43], given that the potential benefits of high-dose IVIg outweigh the risks of the medication and the disease’s natural course.…”
Section: Managementmentioning
confidence: 99%
“…Management of patients with autoimmune diseases, requiring immunosuppressive treatment and concurrent or recent history of malignancy may be challenging and these patients are inappropriate for immunosuppressive treatment options (Enk et al, ). The relationship between cancer and autoimmunity makes IVIG treatment reasonable.…”
Section: Discussionmentioning
confidence: 99%